Assessment of salt intake to consider salt as a fortification vehicle for thiamine in Cambodia. Issue 1 (7th January 2021) - Chan, Kathleen; Gallant, Jelisa; Leemaqz, Shalem; Baldwin, Dare A.; Borath, Mam; Kroeun, Hou; Measelle, Jeffrey R.; Ngik, Rem; Prak, Sophonneary; Wieringa, Frank T.; Yelland, Lisa N.; Green, Tim J.; et al.
Abstract: Thiamine deficiency is a public health issue in Cambodia. Thiamine fortification of salt has been proposed; however, the salt intake of lactating women, the target population, is currently unknown. We estimated salt intakes among lactating women (<6 months postpartum) using three methods: repeat observed‐weighed intake records and 24‐h urinary sodium excretions ( n =  104), and household salt disappearance ( n =  331). Usual salt intake was estimated by adjusting for intraindividual intakes using the National Cancer Institute method, and a thiamine salt fortification scenario was modeled using a modified estimated average requirement (EAR) cut‐point method. Unadjusted salt intake from observed intakes was 9.3 (8.3–10.3) g/day, which was not different from estimated salt intake from urinary sodium excretions, 9.0 (8.4–9.7) g/day ( P  = 0.3). Estimated salt use from household salt disappearance was 11.3 (10.7–11.9) g/person/day. Usual (adjusted) salt intake from all sources was 7.7 (7.4–8.0) g/day. Assuming no stability losses, a modeled fortification dose of 275 mg thiamine/kg salt could increase thiamine intakes from fortified salt to 2.1 (2.0–2.2) mg/day, with even low salt consumers reaching the EAR of 1.2 mg/day from fortified salt alone. These findings, in conjunction with future sensory and stability research, can inform a potential salt fortification program in Cambodia. Abstract : Thiamine deficiency is a public health issue in Cambodia. Thiamine fortification of salt has been proposed; however, the salt intake of lactating women is currently unknown. We estimated salt intakes among lactating women using three methods. Based on these data, a thiamine salt fortification scenario was modeled, which allowed the calculation of a suitable fortification dose of thiamine to add to salt.